2017
DOI: 10.3389/fnut.2017.00041
|View full text |Cite
|
Sign up to set email alerts
|

Amine Metabolism Is Influenced by Dietary Protein Source

Abstract: Growth in world population will inevitably leads to increased demand for protein for humans and animals. Protein from insects and blood plasma are being considered as possible alternatives, but more research on their nutritional quality and health effects is needed. Here, we studied the effect of dietary protein source on metabolism and metabolic amine profiles in serum and urine of mice. Groups of mice were fed semi-purified diets containing 300 g/kg of soybean meal, casein, partially delactosed whey powder, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…From the metabolic pathway analysis, we observed that dietary inclusion of BSF or SBM impacted metabolic pathways as expressed by a differential abundance of amine metabolites. These observations are in agreement with previous findings where pigs fed with insect meal from Tenebrio molitor larvae 51 and mice fed with diets including different protein sources among which insect meal from Tenebrio molitor 21 . The enriched metabolic pathways are mainly related to AA metabolism.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…From the metabolic pathway analysis, we observed that dietary inclusion of BSF or SBM impacted metabolic pathways as expressed by a differential abundance of amine metabolites. These observations are in agreement with previous findings where pigs fed with insect meal from Tenebrio molitor larvae 51 and mice fed with diets including different protein sources among which insect meal from Tenebrio molitor 21 . The enriched metabolic pathways are mainly related to AA metabolism.…”
Section: Discussionsupporting
confidence: 93%
“…An amine-based endophenotype concept was used to evaluate effects of dietary protein source 21 . Products of hydrolysis of dietary protein in the digestive tract and other N-containing constituents present in the diet which are absorbed from the digestive tract, enter the blood circulation and can be further used and metabolized in organs and tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concomitant low serum concentration of the non-essential non-proteinogenic amino acid AABA seems to corroborate the previous finding since AABA may derive from the catabolism of methionine [40]. Further to this, plasma levels of AABA were found to be associated with both the quality and amount of dietary protein [41,42]. Although these findings seem to point towards a poor-quality protein diet or (selective) malabsorption, further studies are needed to clarify the correlation between diet and circulating EAA levels in the context of PF&S.…”
Section: Discussionsupporting
confidence: 85%
“…The concomitant low serum concentration of the non-essential non-proteinogenic amino acid AABA seems to corroborate the previous finding since AABA may derive from the catabolism of methionine [ 39 ]. Furthermore, plasma levels of AABA were found to be associated with both the quality and amount of dietary protein [ 40 , 41 ]. Although these findings seem to point towards a poor-quality protein diet or (selective) malabsorption, further studies are needed to clarify the relationship between diet and circulating EAA levels in the context of PF&S.…”
Section: Discussionmentioning
confidence: 99%